2021
DOI: 10.1126/sciadv.abg8458
|View full text |Cite
|
Sign up to set email alerts
|

Efficient light-emitting diodes based on oriented perovskite nanoplatelets

Abstract: Solution-processed planar perovskite light-emitting diodes (LEDs) promise high-performance and cost-effective electroluminescent devices ideal for large-area display and lighting applications. Exploiting emission layers with high ratios of horizontal transition dipole moments (TDMs) is expected to boost the photon outcoupling of planar LEDs. However, LEDs based on anisotropic perovskite nanoemitters remain to be inefficient (external quantum efficiency, EQE <5%) due to the difficulties of simultaneously contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
78
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(86 citation statements)
references
References 68 publications
(104 reference statements)
0
78
0
Order By: Relevance
“…This led to an enhancement in the outcoupling, and the perovskite LEDs achieved an EQE of 23.6%, which was the highest for LHP LEDs at the time of publication in 2020. [ 230 ]…”
Section: From 3d To 0d: Effect Of Dimensionality On Recombination And...mentioning
confidence: 99%
“…This led to an enhancement in the outcoupling, and the perovskite LEDs achieved an EQE of 23.6%, which was the highest for LHP LEDs at the time of publication in 2020. [ 230 ]…”
Section: From 3d To 0d: Effect Of Dimensionality On Recombination And...mentioning
confidence: 99%
“…Colloidal semiconductor nanoplatelets are materials characterized by large exciton binding energy and oscillator strength, sharp spectral features, and short photoluminescence lifetimes, all properties that make them appealing in devices such as light-emitting diodes and lasers. , The extreme thinness, down to just a few atoms, is both the source of their unique optical properties and a major challenge for their structural characterization. Several studies have demonstrated that nanoplatelets can be much different from an ideal “slice” of the corresponding bulk material: they are structurally less constrained than the bulk and can readily relax through structural distortions and altered lattice constants .…”
mentioning
confidence: 99%
“…Metal halide perovskites are a class of crystalline semiconductors that exhibit excellent optoelectronic properties including tunable emission, high photoluminescence quantum yield (PLQY), and high color purity, making them ideal for electroluminescence applications. A unique advantage of perovskites is that high-quality semiconductor films can be in situ crystallized from precursor solutions by low-cost methods such as spin coating and blade coating. Great advances, including composition and solvent engineering, have been made in the control of in situ grown perovskite films, boosting the external quantum efficiencies (EQEs) of perovskite light-emitting diodes (PeLEDs) to over 23%. …”
mentioning
confidence: 99%